Up from slavery - Washington, Booker T. (Oxford Oxford University Press, 1995)
Born in a Virginia slave hut, Booker T. Washington (1856?1915) rose to become the most influential spokesman for African Americans of his day. In this eloquently written book, he describes events in a remarkable life that began in bondage and culminated in worldwide recognition for his many accomplishments. In simply written yet stirring passages, he tells of his impoverished childhood and youth, the unrelenting struggle for an education, early teaching assignments, his selection in 1881 to head Tuskegee Institute, and more.
Includes bibliographical references (p. [xxiv]-xxv) and index.
Keywords: Washington, Booker T., 1856-1915.